Dried urine spot method for detection of Schistosoma mansoni circulating cathodic antigen in resource-limited settings: a proof of concept study - Zacharia, Abdallah; Makene, Twilumba; Kinabo, Clemence; Ogweno, George; Lyamuya, Faraja; Ngasala, Billy (Frontiers in Immunology, 2023)
Background: Among the challenges in schistosomiasis surveillance and mapping surveys is the lack of a sensitive diagnostic method especially in low transmission setting. Currently, the WHO recommends the use point-of-care circulating cathodic antigen (Schisto POC-CCA) tests for surveillance and mapping of intestinal schistosomiasis. However, Schisto POC-CCA test has its drawbacks, one of which is the timely availability of test kits. One approach to overcoming this challenge is to develop a low-cost sampling method that allows for the collection and transport of urine specimens even in resource-limited settings.Objective: To develop a simple and efficient method for the collection and detection of Schistosoma mansoni (S. mansoni) CCA using urine spotted onto filter paper.To develop a dried urine spot (DUS) method, various dried matrix extraction parameters were tested and optimized using predesigned steps. The parameters include the size of filter paper (determined by the number of punches), volume of solvents, and type of solvent. Moreover, we optimized the incubation conditions (time and temperature). Urine and stool specimens to conduct the experiments were collected from volunteer fishermen in Mwanza and this project staff. Data were entered into the Microsoft Excel spreadsheet and IBM Statistical Package for the Social Sciences, version 20 for analysis.The optimal results were obtained when the procedure was run under the following conditions: Five punches of filter paper containing DUS were dissolved in 150 µl of distilled water and incubated at room temperature for 24 hours in an Eppendorf tube. More than 93% of the assays performed under these conditions produced results that were either comparable to or significantly better than the standard method. This is a provisional file, not the final typeset article Conclusion: This study demonstrates the feasibility of collecting urine specimen (DUS) using filter paper and detecting Schistosoma CCA from DUS specimen using the Schisto POC-CCA cassette test.